PENGARUH CITRA DESTINASI, ELECTRONIC WORD OF MOUTH, DAN SATISFACTION DIMEDIASI LOYALITAS WISATAWAN TERHADAP MINAT BERKUNJUNG KEMBALI KE SABA BADUY - Soelton, Dr. Mochamad (SWOT : Jurnal Ilmiah Ilmu Manajemen, 2024)
This study aims to determine and analyze the effect of destination image, electronic word of mouth, and satisfaction mediated by tourist loyalty on the interest in returning to Saba Baduy. The object of this research is tourists who have visited and want to revisit Saba Baduy as many as 125 respondents. The approach used in this research is a quantitative approach. With the Variance Based Structural Equation Model data analysis method with the Smart-PLS 3.2.9 analysis tool. The results of this study indicate that partially the image of the destination has a positive and significant effect on tourist satisfaction. Electronic word of mouth has a positive and significant effect on revisit interest. Satisfaction has a positive and significant effect on revisit interest. Tourist Loyalty has a positive and significant effect on revisit interest. Visitors has full positive effect and significant of satisfaction mediated by tourist loyalty on Return of Interest in Saba Baduy Tourism Object.